AN OPERATION-LEVEL DYNAMIC CAPACITY SCALABILITY MODEL FOR RECONFIGURABLE MANUFACTURING SYSTEMS - Yu, Zhou-Jing; Shin, Jeong-Hoon; Lee, Dong-Ho (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
This study considers the problem of determining the facility requirements for a reconfigurable manufacturing system to satisfy the demand requirements and the minimum allowable system utilization over a given planning horizon. Unlike the existing capacity planning models for flexible manufacturing systems, the problem considered in this study has both design and operational characteristics since the reconfigurable manufacturing systems have the capability of changing in its hardware and software components rapidly in response to market changes or system changes. To represent the problem mathematically, a nonlinear integer programming model is suggested for the objective of minimizing the sum of facility acquisition and configuration change costs, while the throughputs and utilizations are estimated using a closed queuing network model. Then, due to the problem complexity, we suggest three heuristics, two forward-type and one backward-type algorithms. To compare the performances of the three heuristic algorithms, computation experiments were done and the results are reported.